Assessment Land Use Dynamics in the Border Areas of Ukraine and Poland: a Case Study of Ratne Territorial Community and Lenchna County. - Semeniuk, M.; Fedoniuk, M.; Vovk, Oleksandr P.; Fedoniuk, V.; Merlenko, I. (My University, 2023)
The paper presents an analysis of the land use structure and dynamics in the Ratne Territorial Community (Ukraine) and Łęczna County (Poland) over different time periods. We conducted an examination of topographic maps from various eras, starting from the 1930s, as well as space photographs. Additionally, we utilized tools and services for the automatic classification of satellite images, including CORINE and LUCAS, along with ESA WorldCover. The study evaluated both long-term and recent changes in land use within the studied territories, aiming to identify trends driven by natural and human-induced factors. The findings shed light on the possibilities of utilizing GIS-RS (remote sensing) technologies for effective land use monitoring.
Keywords: Land Cover; Land Use Change; Ratne; Leczna; UA-PL crossborder region; land cover models and services